Subsistence consumption and inflation heterogeneity: Implications for monetary policy transmission in a HANK model - Ulrike Neyer; Daniel Stempel; Alexandra Stevens (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2025)
Households differ in their consumption baskets and inflation rates along the wealth and income distribution. We use German data to show that subsistence consumption is a main driver of these differences: the share of subsistence consumption in overall consumption is significantly higher for households at the lower end of the wealth and income distribution. We construct a price index for subsistence consumption and show that this price index exhibits larger volatility than the price indices constructed for the average consumption basket and the basket of households with average and high income. We then set up a Heterogeneous Agent New Keynesian (HANK) model that incorporates these facts to analyze the consequences of different consumption baskets and inflation heterogeneity for monetary policy transmission. We find that heterogeneous consumption baskets across households weaken monetary policy transmission. This is due to the heterogeneous responses of inflation rates to monetary policy shocks across households, larger labor supply heterogeneity, and a novel indirect transmission channel of monetary policy operating through the real value of subsistence consumption.
Keywords: E12; E21; E31; E32; E52; 330; HANK model; inflation heterogeneity; inequality; monetary policy transmission; subsistence consumption